The evolution of de novo human‐specific microRNA genes on chromosome 21. Issue 2 (3rd March 2022) - Johnson, Hunter R.; Blandino, Jessica A.; Mercado, Beatriz C.; Galván, José A.; Higgins, William J.; Lents, Nathan H.
Abstract: The genetic basis of human uniqueness remains one of the most enduring mysteries in biological anthropology. The goal of this research project was to identify, characterize, and infer the origin and function of novel elements in the human genome that are not functionally shared with other apes. Our approach toward this goal was to utilize a variety of genome alignment tools to discover islands of non‐conserved DNA sequences, followed by theoretical and computational analysis of those regions using synteny sequence analysis. We discovered families of microRNA genes on human chromosome 21 with no detectable orthologs in the other African apes. We then developed a working model of their origin through repeated rounds of segmental duplication occurring within an array of rRNA genes. Target prediction reveals potential roles for these microRNA genes in the embryonic development of the central nervous system. We conclude that the 21p11 region of human chromosome 21 has undergone segmental duplication events that generated de novo microRNA genes from within a field of rRNA genes. These microRNA genes may have played a role in the unique evolutionary trajectory of the human lineage through their modulation of genes involved in embryonic development. Abstract : Segmental duplications on chromosome 21 associate with recombination hotspots and have created new miRNA genes.